Comparison of few statistical models describing castor (Ricinus communis) seed yield response to phosphate fertilizer - MURTHY, I Y; ALIVELU, K (The Indian Journal of Agricultural Sciences, 2013)
Five statistical models, linear response and plateau (LRP), quadratic response and plateau (QRP), logistic, quadraticand square root were compared to describe castor seed yield response to phosphate fertilization under irrigated conditionsof Junagadh and S K Nagar regions. Adjusted R2 values explained the variability in castor seed yield response to Pfertilization, but the optimum phosphorus (Pop) values calculated by these models varied greatly. Overall the QRP followed by LRP model fitted the data with less bias than the other models, and calculated Pop values for Junagadh and S K Nagar (37.1 and 25.6 kg/ha respectively) were comparable with the P doses reported in literature.